(untitled) (Research, Society and Development, 2022)
The objectives of this research were, through a questionnaire, to evaluate the knowledge level of students of the UFCG dentistry course about the tooth bank, use of extracted teeth, capture of teeth for pre-clinical use and, especially, on biosafety in the manipulation of teeth. A questionnaire was applied to students from the first to the fifth year of the course. Results: after applying the questionnaire, it was found that 65.3% of the students interviewed reported difficulty in obtaining the teeth requested in the subjects; with regard to biosafety, 57.6% of the students stated that they had handled the extracted teeth without personal protective equipment, basic health unit and with other colleagues were the options most indicated by students in relation to the search and capture of teeth for use in graduation. There are difficulties in obtaining teeth, most acquired in health units and with other colleagues. An expressive amount of students did not use PPE during the manipulation of a tooth and all are in favor of organ donation.